On the Tasks of Forensic Ecology - N. V. Mikhaleva (Теория и практика судебной экспертизы)
The article analyses the concept of “a forensic examination’s task” as one of the fundamental terms of forensic expertology. The author demonstrates that it is a part of a broader concept of “the subject of forensic examination”. She also reviews the classification of tasks of forensic examination.Next, the article addresses the tasks of forensic ecological examination, which by their nature, as a rule, are diagnostic. The author presents their definition as a set of actions common to this kind of forensic analysis, formed by an expert based on the questions posed to him. These actions are implemented by converting potential evidentiary information about the negative anthropogenic impact on environmental objects contained in the case materials submitted for examination into up-to-date evidentiary information.